Tuning the electrical conductance of metalloporphyrin supramolecular wires - Noori, Mohammed; Aragones, Albert C.; Di Palma, Giuseppe; Darwish, Nadium; Bailey, Steven W.D.; Al-Galiby, Quisy; Grace, Iain; Amabilino, David B.; Gonzalez-Campo, Arántzazu; Díez-Pérez, Ismael; Colin J., Lambert (Nature Publishing Group, 2016)
In contrast with conventional single-molecule junctions, in which the current flows parallel to the long axis or plane of a molecule, we investigate the transport properties of M(II)-5,15-diphenylporphyrin (M-DPP) single-molecule junctions (M=Co, Ni, Cu, or Zn divalent metal ions), in which the current flows perpendicular to the plane of the porphyrin. Novel STM-based conductance measurements combined with quantum transport calculations demonstrate that current-perpendicular-to-the-plane (CPP) junctions have three-orders-of-magnitude higher electrical conductanc than their current in-plane (CIP) counterparts, ranging from 2.10−2 G0 for Ni-DPP up to 8.10−2 G0 for Zn-DPP. The metal ion in the center of the DPP skeletons is strongly coordinated with the nitrogens of the pyridyl coated electrodes, with a binding energy that is sensitive to the choice of metal ion. We find that the binding energies of Zn-DPP and Co-DPP are significantly higher than those of Ni-DPP and Cu-DPP. Therefore when combined with its higher conductance, we identify Zn-DPP as the favoured candidate for high conductance CPP single-molecule devices.